Evolution in Management Trends of Sporadic Vestibular Schwannoma in the United States Over the Last Half-century. Issue 2 (February 2021) - Chan, Stephen A.; Marinelli, John P.; Hahs-Vaughn, Debbie L.; Nye, Chad; Link, Michael J.; Carlson, Matthew L.
Abstract : Objective: Limited data currently characterize management trends of sporadic vestibular schwannoma (VS) in the United States over recent decades. Serving as the primary patient support organization in the United States, the Acoustic Neuroma Association (ANA) facilitates amalgamation of data from patients treated from 1970 through January 2019. The primary objective of the current study was to characterize the evolution in the management of sporadic VS among ANA survey respondents treated over the last half-century. Study Design/Intervention: Cross-sectional survey. Setting/Patients: ANA survey respondents diagnosed with sporadic VS. Main Outcome Measures: Trends in rates of microsurgery, radiosurgery, and observation from 1970 to 2019. Results: Among 953 patients with VS responding during the study period, 876 (92%) were included. Subjects reported the following management strategies: 220 observation (25%), 454 microsurgery (52%), and 193 radiosurgery (22%). The rate of microsurgery decreased from 86–88% from 1970 to 2000 to 44% in the last decade. The proportion of VS observed increased from 7% of all tumors in the 1990s, to 14% in the 2000s, to 33% in the 2010s. The rate of radiosurgery has increased to 28% in the last decades compared with 7% in the 1990s. The rate of subtotal resection in tumors > 2 cm increased from 34% in the 2000s to 60% in the 2010s ( p = 0.0011). Conclusions: Overall, these data support a progression toward fewer patients treated with microsurgery in recent decades. Radiosurgery and observation became increasingly more common after the turn of the century, possibly due to better detection of small and asymptomatic tumors and a greater understanding of the natural history of disease.